Recently, I formulated the following conjecture which seems novel.

Conjecture. For any positive odd integer $n$, we have the identity $$\sum_{j,k=0}^{n-1}\frac1{\cos 2\pi j/n+\cos 2\pi k/n}=\frac{n^2}2.\tag{1}$$

Using Galois theory, I see that the sum is a rational number. The identity $(1)$ has some equivalent versions, for example, $$\sum_{0\le j<k\le n-1}\frac1{\cos 2\pi j/n+\cos 2\pi k/n}=\frac n4\left(n-(-1)^{(n-1)/2}\right)\tag{2}$$ and $$\sum_{1\le j<k\le n-1}\frac1{\cos 2\pi j/n+\cos 2\pi k/n}=-\frac{n-(-1)^{(n-1)/2}}4\left(n+(-1)^{(n-1)/2}2\right).\tag{3}$$ It is easy to check $(1)$-$(3)$ numerically.

Question. How to prove the conjecture?

Your comments are welcome!

  • 1
    $\begingroup$ If we put $n=8$ in the sum under consideration, then up to Maple and Mathematica we face with division by zero. E.g. restart; n := 8; add(add(1/(cos(2*Pi* j/n) + cos(2*Pi* k/n)), k = 0 .. n - 1), j = 0 .. n - 1); Error, numeric exception: division by zero $\endgroup$ – user64494 Aug 1 '19 at 19:20
  • 4
    $\begingroup$ @user64494 but the conjecture was about odd integers $\endgroup$ – Fedor Petrov Aug 1 '19 at 20:59
  • 1
    $\begingroup$ @Fedor Petrov: Thank you. Where do the below proofs use it? $\endgroup$ – user64494 Aug 2 '19 at 6:43
  • 6
    $\begingroup$ @user64494 everywhere:) for even $n$ we indeed have zero denominators (say, for $j=0,k=n/2$ and others), it is senseless. In both below solutions the logarithmic derivative of some polynomial at some point is calculated, and for even $n$ this point would be a root of the polynomial. $\endgroup$ – Fedor Petrov Aug 2 '19 at 8:28
  • $\begingroup$ The identity (1) is a special case of a much more general result, see Theorem 1.2 of my preprint arxiv.org/abs/1908.02155. $\endgroup$ – Zhi-Wei Sun Aug 8 '19 at 3:11

The following argument is very short, but bit tricky, so I remain it along with the previous answer.

Actually this sum quickly factorizes: using $\cos (x+y)+\cos (x-y)=2\cos x\cos y$ and denoting $(j+k)\cdot \frac{n+1}2=a,(j-k)\cdot \frac{n+1}2=b$ we get $$\cos 2\pi j/n+\cos 2\pi k/n=2\cos 2\pi a/n \cdot \cos 2\pi b/n.$$ Here $j, k, a, b$ may be considered as residues modulo $n$ ($\cos 2\pi a/n$ depends only on $a$ modulo $n$), and the map $(j,k)\mapsto (a,b)$ is bijective on $(\mathbb{Z}/n\mathbb{Z})^2$, thus $$ 2\sum_{j,k=0}^{n-1}\frac1{\cos 2\pi j/n+\cos 2\pi k/n}=\sum_{a,b=0}^{n-1}\frac1{\cos 2\pi a/n\cdot \cos 2\pi b/n}=\left(\sum_{a=0}^{n-1}\frac1{\cos 2\pi a/n}\right)^2. $$ It remains to calculate the sum $\sum_{a=0}^{n-1}\frac1{\cos 2\pi a/n}$. Denoting $\omega=e^{2\pi i/n}$ we get $$ \sum_{a=0}^{n-1}\frac1{\cos 2\pi a/n}=\sum_{a=0}^{n-1}\frac{2\omega^a}{1+\omega^{2a}}= \sum_{a=0}^{n-1}\frac{\omega^a+\omega^{(2n+1)a}}{1+\omega^{2a}}=\\ \sum_{a=0}^{n-1} (\omega^a-\omega^{3a}+\dots+(-1)^{(n-1)/2}\omega^{na}+\dots+\omega^{(2n-1)a})=(-1)^{(n-1)/2}n, $$ since the geometric progressions $\sum_{a=0}^{n-1} \omega^{ma}$ sums up to $$\sum_{a=0}^{n-1} \omega^{ma}=\begin{cases}0& \text{for}\, m\, \text{not divisible by}\, n\\ n& \text{for}\, m\, \text{divisible by}\, n. \end{cases}$$


Let $T_n$ be the $n$-th Chebyshev polynomial, so that $$T_n(x)-1=\prod_{j=1}^n(x-\cos 2\pi j/n).$$ Taking a logarithmic derivative we have $$\sum_{j=0}^{n-1}\frac{1}{x-\cos 2\pi j/n}=\frac{T_n'(x)}{T_n(x)-1}.$$ For $x=-\cos 2\pi k/n$, we easily find $T_n(x)=-1$. We therefore have $$\sum_{j=0}^{n-1}\frac{1}{\cos 2\pi k/n+\cos 2\pi j/n}=\frac{T_n'(-\cos 2\pi k/n)}{2}.$$ Now the derivative of $T_n$ is equal to $nU_{n-1}$, where $U_{n-1}$ is the Chebyshev polynomial of the second kind, satisfying $U_{n-1}(\cos t)=\frac{\sin nt}{\sin t}$.

For $k\neq 0$, at $t=2\pi k/n+\pi$, so that $\cos t=-\cos 2\pi k/n$, we get $U_{n-1}(-\cos 2\pi k/n)=\frac{\sin(2\pi k+n\pi)}{\sin(2\pi k/n+\pi)}=0$. For $k=0$, we have to take a limit at $t\to\pi$ and we find $U_{n-1}(1)=n$. Therefore we get $$\sum_{k=0}^{n-1}\sum_{j=0}^{n-1}\frac{1}{\cos 2\pi k/n+\cos 2\pi j/n}=\frac{T_n'(1)}{2}=\frac{n^2}{2}.$$


Denote $\omega=e^{2\pi i/n}$, then $\Omega=\{\omega^k:k=0,\ldots,n-1\}$ is the set of roots of the polynomial $f(t):=t^n-1$, $-\Omega=\{-\omega^k:k=0,\ldots,n-1\}$ the set of roots of $g(t):=t^n+1$. We start with the identity $$ \eta(t):=\sum_{k=0}^{n-1}\frac1{t+\omega^k}=\frac{g'(t)}{g(t)}=\frac{nt^{n-1}}{t^n+1}. \quad\quad\quad\quad\quad\quad\quad\quad(1) $$ Your initial sum is $$2\sum_{j,k=0}^{n-1}\frac1{\omega^k+\omega^{-k}+\omega^j+\omega^{-j}}=2\sum_{j,k=0}^{n-1}\frac1{(\omega^k+\omega^{j})(1+\omega^{-j-k})}.$$ Fix $j+k\equiv a\pmod n$, and change the order of summation from $(j,k)$ to $(a,k)$. We get $$ \sum_{a=0}^{n-1}\frac1{1+\omega^{-a}}\sum_{k=0}^{n-1}\frac2{\omega^k+\omega^{a-k}}. $$ Consider the inner sum. Denote $t_{\pm}(a)=\pm i\omega^{a/2}$ so that $$\frac2{\omega^k+\omega^{a-k}}=\frac1{\omega^k+t_+(a)}+\frac1{\omega^k+t_-(a)}$$ and by (1) we get $$ \sum_{k=0}^{n-1}\frac2{\omega^k+\omega^{a-k}}=n\left(\frac{t_+(a)^{n-1}}{t_+(a)^n+1}+\frac{t_-(a)^{n-1}}{t_-(a)^n+1}\right)=nt_+(a)^{n-1}=n(-1)^{\frac{n-1}2}\omega^{\frac{n-1}2 a}. $$ So it remains to calculate the sum $$ n(-1)^{\frac{n-1}2}\sum_{a=0}^{n-1} \frac{\omega^{\frac{n-1}2 a}}{1+\omega^{-a}}= n(-1)^{\frac{n-1}2}\sum_{z\in \Omega}\frac{z^{\frac{n+1}2}}{1+z}. $$ Denote $m=\frac{n+1}2$. We get $$ \sum_{z\in \Omega} \frac{z^m}{z+1}= \sum_{z\in \Omega} \frac{z^m-(-1)^m+(-1)^m}{z+1}= (-1)^m\cdot \frac{n}2+\sum_{z\in \Omega} (z^{m-1}-z^{m-2}+\ldots+(-1)^{m-1})=\\ (-1)^m\cdot \frac{n}2+(-1)^{m-1}\cdot n=(-1)^{m-1}\cdot \frac{n}2 $$ and your conjecture follows.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for?Browse other questions tagged or ask your own question.